PERANAN NOTARIS DALAM PEMBANGUNAN DAERAH KHUSUS IBUKOTA JAKARTA: ANALISIS KEBIJAKAN PENGENAAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN TERHADAP PERJANJIAN PENGIKATAN JUAL-BELI - Taufik Hidayat; Iskandar Muda; Mohammad Ryan Bakry (Universitas Labuhanbatu, 2022)
This study aims to determine the role of a Notary in the imposition of acquisition on Land and Building Rights (BPHTB) DKI Jakarta for the transfer of rights to land and buildings with the Sale and Purchase Agreement (PPJB) and to determine the legal position of the Sale and Purchase Agreement (PPJB). in the transfer of land and building rights to be subject to BPHTB. This research is a normative juridical research conducted by examining library materials or secondary legal materials as the basic material for research.The results of this study indicate the role of the Notary/Land Deed Making Official (PPAT) in the development of DKI Jakarta through the imposition of Customs on the Acquisition of Land and Building Rights (BPHTB) on land and building sale and purchase transactions with PPJB is very meaningful/big, because indirectly is the party that oversees/controls or acts as a gateway so that BPHTB tax debt payments are fulfilled by BPHTB taxpayers as financing for regional development, starting from spending on employees/state institutions to infrastructure development, education costs, health costs, and the construction of public facilities And the position of the Sale and Purchase Agreement of Land Rights made by a Notary is valid and binding if it is based on the terms of the validity of the agreement and is made by or before public officials who are authorized to do so at the place where the deed was made as regulated in Article 15 of the Law-Law Number 30 of 2004 and its amendment Number 2 of 2014 concerning the Position of NotaryKeywords: BPHTB, Notary; Sale and Purchase Agreement (PPJB); Tax.Â